Oral vocabulary as a predictor of English language proficiency among Malaysian Chinese preschool children - Hooi, San Phoon; Anna Christina Abdullah (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
The vocabulary of children is an important indication of their language ability during the preschool years. This study examined whether oral vocabulary is a good predictor of the English language proficiency of Malaysian Chinese preschoolers by examining the correlation of oral vocabulary and English language proficiency. A total of 204 Chinese preschoolers aged between 3 to 6 years participated in this study. A parental report was used to gauge the English language proficiency level of the children; while a set of stimulus pictures containing 160 basic and easy vocabularies were used to determine the oral vocabulary abilities of the children. The results showed that preschoolers’ oral production of English vocabulary had a significant and positive correlation with their English language proficiency. Older children showed more correct production of English vocabulary compared to younger children. There were no gender effects in their oral productions. The findings of the present study could serve as a way to gather information on preschoolers’ level of English language proficiency, to inform instructional practice and to rule out second language learning problems or language delay.